Porosity and water retention characteristics of humid tropical soil at specific depths of different land use practices - Tochukwu, Amanze Chikamnele; Olughu, Ibe, Kalu; Ogochukwu, Nwosu Comfort; Fransisca, Eluagu Kelechi; Ekeoma, Ukabiala Maduabuchi; Patience, Okoror (Review of Environment and Earth Sciences, 2024)
Soil porosity and water retention characteristics influence permeability and water dynamics of soils. This study examines soil porosity and water retention characteristics of different land-use practices at specific depths. The split-plot experiment under Randomized Complete Block Design had land-use as the main plot factor at four levels, and depth, the sub-plot factor at five levels. Soil samples were collected at specific depths of nine randomly selected points in each land-use. Samples were analyzed in a laboratory. Data were analyzed for variance and correlation using Statistical Analysis System (SAS) and Statistical Package for the Social Sciences (SPSS) software, respectively. Results showed that treatments varied significantly (P≤5 %); oil palm plantation (OP) had the highest water content at 0 – 20 and 20 – 40 cm depths, while continuously cultivated land (CC) had the lowest water content across depths. Also, OP had the highest total porosity at 0 – 80 cm depths, while grassland (GL) had the lowest total porosity across depths. The CC had the highest macro-porosity across depths, while forest land (FL) had the lowest accordingly. Porosity decreased with increase in depth, while water retention characteristics increased with depth. There was significant (P≤5 %) negative relationship between soil porosity and water retention characteristics at the land-use practices. The order of optimum soil porosity and water retention capacity of the land-use practices was OP ˃ FL ˃ GL ˃ CC, while the strength of the relationship between porosity and water retention characteristics was greatest at the soil under CC.